Was ist verantwortliche Rede von Gott? - Lange, Dietz (Zeitschrift für Theologie und Kirche, 1997)
Speaking responsibly about God means responding to God's 'Word' as well as being answerable to humans. That implies commitment to God in faith and to humans in love, which is to be mediated by detached reasoning. This apparent contradiction between end and means can be resolved only by 'performative' language authorized by God Himself. That leaves all actual human speech in an unavoidable dialectical tension of commitment and rationality.